1998
DOI: 10.1088/0953-8984/10/42/014
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature thermal and high-pressure studies of CePd and

Abstract: The anomalous properties of the Kondo lattice are compared with the well behaved Kondo system, CePd. The low-temperature thermal expansion of CePd is in agreement with previous heat capacity data, showing a ferromagnetic transition at and a second transition at 3.5 K probably due to reorientation of the magnetic moments. The Grüneisen factor, calculated from thermal-expansion and heat capacity is , the same as the Grüneisen factor calculated from the pressure dependence and comparable to a previous measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Ce 6p states were added to increase the quality of the basis set. The spatial extension of the basis orbitals, controlled by a confining potential (r/r 0 ) 4 , was optimized to minimize the total energy. The self-consistent potentials were carried out on a k mesh of 18 k points in each direction of the Brillouin zone, which corresponds to 550 k points in the irreducible zone.…”
Section: Methods Of Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ce 6p states were added to increase the quality of the basis set. The spatial extension of the basis orbitals, controlled by a confining potential (r/r 0 ) 4 , was optimized to minimize the total energy. The self-consistent potentials were carried out on a k mesh of 18 k points in each direction of the Brillouin zone, which corresponds to 550 k points in the irreducible zone.…”
Section: Methods Of Calculationsmentioning
confidence: 99%
“…The temperature-dependent resistivity of CeAgSb 2 is typical of a Kondo lattice system. Preliminary inelastic neutron scattering measurements indicate a Kondo temperatur T K between 60 and 80K [4]. The magnetoresistence of CeAgSb 2 is either positive or negative, depending on the temperature and orientation of the applied field.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…3,12 Several different groups have investigated the magnetic properties of CeAgSb 2 with conflicting results for the interpretation of the magnetic ground state. 6,7,[13][14][15][16] For instance, Muro et al 6 suggested a ferrimagnetic ground state in polycrystalline samples with a spin-flip field of about 1.3 T. However, this result disagrees with muon spin rotation ͑SR͒ measurements where spectra in both the ordered state and paramagnetic state indicate a single crystallographic and magnetic muon site. 16 Nevertheless, in accordance with SR measurements, 16 it is very difficult in polycrystalline samples to differentiate between a simple ferromagnetic structure and ©2005 The American Physical Society 104428-1 a complex antiferromagnetic structure with a resultant ferromagnetic component.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally observed that ␣ mag (T) exhibits a peak, similar to that observed in the heat capacity, at the magnetic ordering temperature. 27 Figure 6 shows ␣ 4 f (T)a sa function of temperature for CeSbNi x alloys. ␣ 4 f (T) of CeSb ͑in zero field͒ exhibits a sharp peak at 15.4 K, followed by a second broad peak at 12.9 K. The sharp peak in ␣ 4 f (T)i s due to the first-order phase transition from the paramagnetic to antiferroparamagnetic ͑AFP, kϭ2/3,↑᭺↓; the open circle shows the position of the paramagnetic plane͒ phase.…”
Section: Thermal Expansionmentioning
confidence: 99%